(untitled) (Semiárida, 2018)
The “pajonal” is a typical grassland of the central region of Buenos Aires, a province of Argentina, being dominated by Paspalum quadrifarium, a tall-t ussock grass. During the past five centuries, this grassland has been used as a feeding resource for domestic cattle. This traditional usage, which is often accompanied by the practice of periodic burning, gives way to impacts on various aspects of ecosystem structure and dynamics at different scales. Remote sensing has proved to be a powerful tool able to monitor land cover changes at regional scale and assess landscape fragmentation. This work was carried out in the central region of the original distribution of “pajonal” in the Flooding Pampa of Buenos Aires province. A Landsat TM image, radiometrically and atmospherically calibrated, was used. The supervised classification of the reconstructed images was done by the maximum likelihood method. Assessment of landscape structure by spatial metrics of “pajonal” grassland was performed by FRAGSTATS 4 .1 computer programme. Classification was accomplished with a very good accuracy, and evaluation of key metrics allowed the identification of a gradient related to the “pajonal” conservation condition.